A Comparative Study of Social Scene Parsing Strategies between Children with and without Autism Spectrum Disorder - Song, Chen; Wang, Aosen; Doody, PhD, Kathy Ralabate; Hartley- McAndrew, MD, Michelle; Mertz, MBA, Jana; Lin, PhD, Feng; Xu, PhD, Wenyao (North American Journal of Medicine and Science, 2016)
Autism spectrum disorder (ASD) is a complex developmental disability characterized by deficits in social interaction. Gaze behavior is of great interest because it reveals the parsing strategy the participant uses to achieve social content. The legacy features in gaze fixation, such as time and area-of-interest, however, cannot comprehensively reveal the way the participant may cognize the social scene. In this work, we investigate the dynamic components within the gaze behavior of children with ASD upon the carefully-selected social scene. A cohort of child participants (n = 51) were recruited between 2 and 10 years. The results suggest significant differences in the social scene parsing strategies of children with ASD, giving added insight into the way they may decode and interpret the social scenarios. [N A J Med Sci. 2016;9(3):96-103. DOI: 10.7156/najms.2016.0903096]